Scientific Activity and Contribution of Voldemārs Dāle (1922–2008), Honorary Doctor of the Latvian Academy of Sciences, to the Development of Power Engineering - Austra Avotiņa (History of Engineering Sciences and Institutions of Higher Education)
Honorary Doctor (Dr. h. c.) of the Latvian Academy of Sciences (LAS), long-time leading researcher of the Institute of Physical Energetics, Professor Voldemārs Dāle (1922–2008) devoted his entire working life to science. The most important field of V. Dāle’s research was the use of mathematical methods and computer technology in the dynamic optimization of power engineering development. The main areas of his scientific work include planning and forecasting methods of power system development; research on development problems of the Latvian and Baltic energy systems; methods of mathematical modelling of power systems considering the environmental factors. A monograph on research results in the optimization of electrical network development published in 1964 written by a group of three scientists, including V. Dāle, received the State Prize of the Latvian Soviet Socialist Republic (LSSR), which was awarded in 1965.